Between the galley and plantation: the rhetorical construction of English servants in the seventeenth century. Issue 1 (2nd January 2023) - Smith, Brian
ABSTRACT: This paper seeks to show that due to the transformations of the working class in seventeenth-century England, a discursive tradition emerged in devotional literature and servant manuals that valorized a specific form of servitude. By embodying the will of their masters, servants were free. By resisting their master's will, they resembled either African slaves forced to toil on the plantations or galley slaves compelled to row for Muslim masters. These racialized forms of slavery were designed to generate a powerful intuition of idealized servitude. Servants who complained or those who sought to become hirelings, or independent free labourers, risked becoming worse than a slave. In short, the imagery of plantation and galley slaves was strategically utilized to construct a pliable and obedient working class in England. In short, by accepting one's station and willingly submitting to a master English servants performed Christian liberty.